1995
DOI: 10.21273/jashs.120.4.558
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethephon Spray Treatments on Mechanical Harvesting and Oil Composition of `Arbequina' Olives

Abstract: Ethephon was applied at 0, 625, 1250, 1875, and 2500 m·gliter-1 in 2 consecutive years to `Arbequina' olive trees to determine its effect on fruit removal with mechanical harvesting and on fruit oil composition. Ethephon increased the mechanical harvesting efficiency by 20%. Ethephon at 1250 and 1875 mg·liter-1 were the optimum treatments, resulting in 63% and 66% of the olives being mechanically harvested, respectively, with a prehar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…The results of GA 3 treatments are similar to those obtained by other authors [11][12][13] who found that the GA 3 treatment slightly increased the average yield of date palm trees. The results of ethephon treatments also agree with those of researchers [2,15] who found that the application of ethephon had no significant effect on yield of olive and date palm trees, respectively.…”
Section: Effect Of the Growth Regulators On The Fruit Weightsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of GA 3 treatments are similar to those obtained by other authors [11][12][13] who found that the GA 3 treatment slightly increased the average yield of date palm trees. The results of ethephon treatments also agree with those of researchers [2,15] who found that the application of ethephon had no significant effect on yield of olive and date palm trees, respectively.…”
Section: Effect Of the Growth Regulators On The Fruit Weightsupporting
confidence: 90%
“…The past few years have witnessed significant advances in the use of synthetic and natural plant bioregulators for the improvement of crop performance in citrus [1,2], apple [2][3][4][5] and avocado [6]. Date palm trees (Phoenix dactylifera L.) are among the most cultivated horticultural crops in the United Arab Emirates.…”
Section: Introductionmentioning
confidence: 99%
“…Little has been published on the effect of abscission agent application relative to both FDF and harvest efficiency. Birger et al (2008) and Tous et al (1995) found a correlation between FDF and harvest efficiency in oil olives harvested at an advanced stage of ripening, but not in green table olives. Lavee et al (1982) showed that harvesting efficiency and leaf drop are varietysensitive, and Klein et al (1978) demonstrated the sensitivity of the system to irrigation practices and temperature.…”
Section: Discussionmentioning
confidence: 97%
“…High harvest efficiencies are reached when trunk shaking is accompanied by rod beating. The effect of abscission agents on harvest efficiency is negligible and in most cases inconsistent, and they can probably be omitted, especially when cost-benefit considerations are taken into account together with the potential damage from defoliation (Ben-Tal and Lavee, 1976;Tous et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The use of ethylene-releasing chemicals to increase removal rates of mechanical shakers has been widely studied in many countries and for many years (Lavee and Haskal, 1975;Martin et al, 1981;Tous et al, 1995;Vitagliano, 1975). However, removal efficiency in research trials using ethylenereleasing chemicals has been erratic (Martin et al, 1981), perhaps as a result of the variability in loosing product uptake and breakdown under natural conditions (Denney and Martin, 1994;Lavee and Haskal, 1975).…”
mentioning
confidence: 99%